Stress Release of Single Crystal Arrays Bridged by SAM Interface Toward Highly Mechanically Durable Flexible Perovskite NIR Photodetector - Yin, Xing (Advanced materials (Deerfield Beach, Fla.), 2025)
© 2025 Wiley‐VCH GmbH.